2010
DOI: 10.1016/j.jjcc.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of intravenous nicorandil on hemodynamics in patients hospitalized with acute decompensated heart failure

Abstract: Intravenous administration of nicorandil, by bolus injection followed by continuous infusion, improves PAWP and CI in ADHF patients immediately and continuously as a potent vasodilator with combined preload and afterload reduction. These results demonstrate that nicorandil is a safe and effective new medication for the treatment of ADHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…20 Tanaka et al reported that nicorandil can reduce preload in lower infusion rates of <0.1 mg · kg -1 · h −1 , but for further improvement in the afterload and cardiac output via KATP channel opening, a higher infusion rate of 0.2 mg · kg -1 · h −1 would be more appropriate. 7 However, their study was monotherapy of nicorandil, whereas continuous nicorandil infusion at 0.1-0.15 mg · kg -1 · h −1 as in the present study may be able to improve preload and afterload in clinical use (ie, combined therapy with diuretics or other vasodilators). No pronounced hypotension occurred with this nicorandil regimen.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…20 Tanaka et al reported that nicorandil can reduce preload in lower infusion rates of <0.1 mg · kg -1 · h −1 , but for further improvement in the afterload and cardiac output via KATP channel opening, a higher infusion rate of 0.2 mg · kg -1 · h −1 would be more appropriate. 7 However, their study was monotherapy of nicorandil, whereas continuous nicorandil infusion at 0.1-0.15 mg · kg -1 · h −1 as in the present study may be able to improve preload and afterload in clinical use (ie, combined therapy with diuretics or other vasodilators). No pronounced hypotension occurred with this nicorandil regimen.…”
Section: Discussionmentioning
confidence: 55%
“…In a study of 99 patients with AHFS treated with a bolus injection of nicorandil 0.2 mg/kg followed by continuous infusion at 0.05-0.2 mg · kg -1 · h −1 , Tanaka et al reported that hemodynamics was stable throughout the treatment with nicorandil in all patients except 1 (1%) who exhibited a decrease in BP that did not require discontinuation of the nicorandil infusion. 7 Several reports 6,7,19 have noted that nicorandil significant decreased SBP in patients with high baseline SBP but not in those with low to normal baseline SBP, indicating that nicorandil treatment is safe and efficacious. In this study, all patients in the Nicorandil group received a bolus injection of nicorandil at 0.1-0.2 mg/kg followed by continuous nicorandil infusion at 0.1 mg · kg -1 · h −1 for at least 3 days, during which time the infusion rate of nicorandil was adjusted at the discretion of each physician according to SBP, symptoms or clinical signs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, several studies showed that nicorandil did not decrease systolic BP (SBP) significantly in patients with low to normal SBP, while it did decrease SBP remarkably in patients with an elevated baseline SBP. 14 26 27 Therefore, single bolus intravenous injection of nicorandil can be used safely, possibly provide a longer duration of hyperaemia compared with IC nicorandil, 28 and be hopefully useful for FFR measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrates are commonly used for the management of AIHF in the acute phase (4)(5)(6)(7). Nicorandil (N-(2-hydroxyethyl)-nicotinamide nitrate; Chugai), a hybrid of an adenosine triphosphate (ATP)-sensitive potassium channel opener and a nitrate, is also used to treat patients with AIHF to improve the recovery of postischemic cardiac contractile function (8,9). Nicorandil exerts a vasodilatory effect on the systemic veins, and it also dilates arteries, including the peripheral arteries, by opening ATPsensitive potassium channels (10)(11)(12).…”
mentioning
confidence: 99%